(untitled) - Keller, Gerald; Gerald Keller (Pacific Grove, CA)
Gerald Keller's new APPLIED STATISTICS WITH MICROSOFTÂđ EXCEL integrates Excel into the general introductory statistics course. Keller, the co-author of the market-leading STATISTICS FOR MANAGEMENT AND ECONOMICS, Fifth Edition, incorporates his proven three-step problem-solving process throughout this book. The first step, "Identify," is the work a statistician does before the calculations are performed, which entails organizing the experiment, gathering the data, and deciding which statistical techniques to employ. The second step, "Compute," is the computation with Excel. In this step, Keller shows the manual calculation for the simplest of techniques only. For example, he describes how to calculate the sample mean, variance, and standard deviation, how to compute the z-interval estimate of, and the z-test of. The third step, "Interpret," is the interpretation of the computer output, which requires an understanding of statistical concepts
Includes bibliographical references and index
Keywords: Management; Economics; Statistics